Effective Non-Operative Management of Lacertus Syndrome: Two Case Reports and A Review of Literature: Non-Operative Management of Lacertus Syndrome - Ghalimah, Bayan; Bokhary, Omar; Bukhari, Abdulrahman (J Med Rehab Sci, 2025)
Lacertus syndrome (LS) is a condition characterized by median nerve entrapment at the Lacertus Fibrosus (LF), a fibrous band distal to the elbow joint, presenting with pain, numbness, and weakness in the forearm and hand. Due to its rarity, LS is often overlooked in the diagnosis of these symptoms. Management can be surgical or non- surgical, depending on preference and symptom severity. Most studies published on this syndrome showed symptom relief only after surgical intervention. We present two case reports describing the successful non-surgical management of lacertus syndrome in two males in the dental field who presented with bilateral and unilateral LS. Grip strength, pain score, and functional scores were used to assess pre- and post- treatment outcomes. Treatment involved a combination of myofascial release, nerve gliding exercises, and strengthening protocols. The grip strength of the affected hand improved significantly in both patients. In the first patient, the grip strength of the right hand increased from 12 kg to 38 kg, while the left hand’s grip strength improved from 36 kg to 48 kg. In the second patient, grip strength progressed from being unable to perform any grip strength to 46 kg. Additionally, the Visual Analog Scale (VAS) score improved for both patients, decreasing from 8/10 to 1/10. To our knowledge, these are the first two cases in the literature managed successfully without surgical intervention. The successful management of lacertus syndrome in both patients illustrates the importance of a multifaceted, non-surgical approach. This report supports the notion that tailored conservative treatments can lead to significant improvements in function and quality of life.